From Rate-Limiting Enzyme to Therapeutic Target: The Promise of NAMPT in Neurodegenerative Diseases - Zhu, Yumeng; Xu, Ping; Huang, Xuan; Shuai, Wen; Liu, Li; Zhang, Shuai; Zhao, Rui; Hu, Xiuying; Wang, Guan (Frontiers in Pharmacology, 2022)
Nicotinamide phosphoribosyltransferase (NAMPT) is the rate-limiting enzyme in the nicotinamide adenine dinucleotide (NAD) salvage pathway in mammals. It is of great significance in the metabolic homeostasis and cell survival via synthesizing nicotinamide mononucleotide (NMN) through enzymatic activities, serving as a key protein involved in the host's defense mechanism. The NAMPT metabolic pathway connects NAD-dependent sirtuin (SIRT) signaling, constituting the NAMPT-NAD-SIRT cascade, which is validated as a strong intrinsic defense system. Neurodegenerative diseases belong to the central nervous system (CNS) disease that seriously endangers human health. The World Health Organization (WHO) proposed that neurodegenerative diseases will become the second leading cause of human death in the next 2 decades. However, effective drugs for neurodegenerative diseases are scant. NAMPT is specifically highly expressed in the hippocampus, which mediates cell self-renewal and proliferation, and oligodendrocytes synthesis by inducing the biosynthesis of NAD in neural stem cells/progenitor cells. Owing to the active biological function of NAMPT in neurogenesis, targeting NAMPT may be a powerful therapeutic strategy for neurodegenerative diseases. This study aims to review the structure and biological functions, the correlation with neurodegenerative diseases, and treatment advance of NAMPT, aiming to provide a novel idea for targeted therapy of neurodegenerative diseases.